Cigarette Smoke Exposure Attenuates Cytokine Production by Mouse Alveolar Macrophages - Gaschler, Gordon J; Zavitz, Caleb C. J; Bauer, Carla M. T; Skrtic, Marko; Lindahl, Maria; Robbins, Clinton S; Chen, Biao; Stampfli, Martin R (American journal of respiratory cell and molecular biology, 2008)
Alveolar macrophages (aMs) play a central role in respiratory host defense by sensing microbial antigens and initiating immune-inflammatory responses early in the course of an infection. The purpose of this study was to investigate the effect of cigarette smoke exposure on aMs after stimulation of innate pattern recognition receptors (PRRs) in a murine model. To accomplish this, C57BL/6 mice were exposed for 8 weeks using two models of cigarette smoke exposure, nose-only or whole-body exposure, and aMs isolated from the bronchoalveolar lavage. After stimulation of aMs with pI:C, a mimic of viral replication, and bacterial cell-wall constituent LPS, aMs from cigarette smoke-exposed mice produced significantly attenuated levels of the inflammatory cytokines TNF-alpha and IL-6, and the chemokine RANTES. This attenuation was specific to the aM compartment, and not related to changes in aM viability or expression of Toll-like receptor (TLR)3 or TLR4 between groups. Furthermore, aMs from smoke-exposed mice had decreased cytokine RNA as compared with aMs from sham-exposed mice. Mechanistically, this was associated with decreased nuclear translocation of the proinflammatory transcription factor NF-kappaB, and increased activator protein-1 nuclear translocation, in aMs from smoke-exposed mice. Attenuated cytokine production was reversible after smoking cessation. Cigarette smoke exposure also attenuated TNF-alpha production after stimulation with nucleotide-oligomerization domain-like receptor agonists, showing that the effect applies more broadly to other PRR pathways. Our data demonstrate that cigarette smoke exposure attenuates aM responses after innate stimulation, including pathways typically associated with bacterial and viral infections.